Bibliography for Conference on Thinking. Cambridge, Massachusetts, August 1984 - Cipollone, Anthony, Comp.; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Drawn from several comprehensive bibliographies and computer searches of volumes by speakers at the Conference on Thinking, this brief bibliography presents resources for researchers and practitioners interested in the areas of cognitive and critical thinking skills. The materials are divided into the following topic areas: (1) general, (2) problem solving, (3) creativity, (4) philosophy of mind and thinking, (5) learning to learn, (6) pictorial/oral/written communication, (7) artificial intelligence and computers, (8) brain functioning, (9) intelligence, (10) reasoning/critical thinking, (11) cognitive development, and (12) understanding. (HTH)
Availability: Harvard Graduate School of Education, Gutman Library, 6 Appian Way, Cambridge, MA 02138 ($10.00, paper only).
Researchers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Artificial Intelligence; Bibliographies; Cognitive Processes; Communication (Thought Transfer); Computers; Creative Thinking; Creativity; Critical Thinking; Learning Processes; Neurological Organization; Problem Solving; Brain Functions; Reference Materials, Bibliographies